The Improvement of English Speaking Skills for Elementary School Students Through the Role Play Method: A Study at a Course Center in Sidrap Regency - Hermansyah, Sam; Astinah, Andi; Mohamed, S. H. Sheik; Nirmala, M. (Indonesian Scientific Publication, 2024)
English is an essential skill in the era of globalization, supporting students’ academic development and communication abilities from an early age. However, teaching English to elementary school children still faces several challenges, including the lack of engaging and effective teaching methods. This study aims to improve students’ English-speaking skills through the implementation of the role-play method at a language course in Sidrap Regency. This research employs a descriptive approach, involving elementary school students as subjects. The training sessions were conducted in multiple phases, designed to be interactive and enjoyable, with role-playing scenarios based on real-life contexts. Evaluation results indicate that the role-play method significantly enhances students’ motivation to learn English, their vocabulary comprehension, and their ability to construct and pronounce simple sentences. The study concludes that the role-play method can be an effective teaching strategy to improve English-speaking skills among elementary school students. The findings of this research are expected to serve as a reference for educators and educational institutions in developing creative and applicable teaching methods.